1987
DOI: 10.1007/bf02100011
|View full text |Cite
|
Sign up to set email alerts
|

Oligoglyceric acid synthesis by autocondensation of glyceroyl thioester

Abstract: Summary: The autocondensation of the glyceroyl thioester, S-glyceroyl-ethanethiol, yielded oligoglyceric acid. The rates of autocondensation and hydrolysis of the thioester increased from pH 6.5 to pH 7.5 in 2,6-lutidine and imidazole buffers. Autocondensation and hydrolysis were much more rapid in imidazole buffers as compared to 2,6-lutidine and phosphate buffers. The efficiency of ester bond synthesis was about 20% for 40 mM S-glyceroyl-ethanethiol in 2,6-lutidine and imidazole buffers near neutral pH. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This method allows us to prepare poyglyceric acid of different sizes and enantiomeric compositions for chemical studies of this polymer which may have functioned as an autocatalyst in the origin of life (Weber, 1987a;Weber, 1987b). Our studies show that L-glyceric acid was converted much more rapidly to an insoluble polymer than racemic DL-glyceric acid.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This method allows us to prepare poyglyceric acid of different sizes and enantiomeric compositions for chemical studies of this polymer which may have functioned as an autocatalyst in the origin of life (Weber, 1987a;Weber, 1987b). Our studies show that L-glyceric acid was converted much more rapidly to an insoluble polymer than racemic DL-glyceric acid.…”
Section: Discussionmentioning
confidence: 90%
“…These model studies showed the conversion of glyceraldehyde and a thiol to activated monomerslactoyl, glyceroyl and alanyl thioesters -which have the energy needed for condensation to polyesters and polypeptides (Weber and Orgel, 1979;Weber 1987a). This ability of glyceraldehyde to act as a source of activated monomers, which possess both the energy and matter needed for polymer synthesis, provided the central idea of a new hypothesis of the origin of life -called the triose model (Weber 1987b).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The synthesis of [14C]glyceric acid and the preparation of the acid form of L-glyceric were described previously (Weber, 1987b(Weber, , 1989. [14C]Methanol was purchased from New England Nuclear.…”
Section: Methodsmentioning
confidence: 99%